Artificial Intelligence in Construction Management - Syed Abdul Kareem Shajahan (International Journal of Scientific Research in Civil Engineering, 2022)
Artificial intelligence (AI) is a process that combines the power of deep learning and fast processing to solve various construction problems. It can help identify and prevent defects and improve the efficiency of the project by analyzing large amounts of data. It can also provide various solutions for risk assessment and prediction. Through the combination of deep learning and fast processing, AI can help identify and prevent defects and improve the efficiency of the project by analyzing large amounts of data. It can also provide various solutions for risk assessment and prediction. Some of these include knowledge discovery, root cause analysis, and prediction. The rapid emergence and evolution of AI has greatly improved the efficiency and productivity of construction projects. This has allowed industrial participants to operate more safely and efficiently, which has increased the competitiveness of the construction industry globally.